PHYSICOCHEMICAL ASPECTS OF THE SORBATION OF CERTAIN RARE METAL IONS USING GRANULAR IONITES - Adinaeva Dilnoza Kurbanali kizi; Kattayev Nuritdin Torayevich; Akbarov Hamdam Ikromovich (Scholar Express Journal, 2023)
This article explores the physicochemical aspects of the sorption process of certain rare metal ions using granular ionites. The study delves into the ion exchange mechanism, selectivity, and the influence of various factors on the sorption efficiency. The research employs a combination of literature analysis and experimental methods to provide comprehensive insights into the sorption behavior of rare metal ions on granular ionites
Keywords: Rare metal ions; sorption; granular ionites; physicochemical aspects